Lifting the shadow : reshaping memory, race, and slavery in U.S. museums - Sodaro, Amy, 1975- (New Brunswick, New Jersey : Rutgers University Press, 2025)
"Lifting the Shadow: Reshaping Memory, Race, and Slavery in U.S. Museums examines a small but significant wave of new U.S. memorial museums that focus on slavery and its ongoing violent legacies, including the Smithsonian National Museum of African American History and Culture, Montgomery's Legacy Museum: From Enslavement to Mass Incarceration and Greenwood Rising, which commemorates the 1921 Tulsa Race Massacre. These museums are challenging historical narratives of slavery and race by placing racial oppression at the center of American history and linking historical slavery to contemporary racial injustice, but they have opened in a period marked by growing racial tension, white nationalism and political division. Sodaro examines how the violence of U.S. slavery and its lasting legacies is negotiated in these museums, as well as their potential to contribute to the development of a more critical historical memory of race in the U.S. at this particularly volatile sociopolitical moment"--
Introduction : Memory in post-postracial America -- Race and memory in the United States : A shifting memorial landscape -- Telling "America's Story" : The National Museum of African American History and Culture -- "Shine the light of truth" : The Legacy Museum -- "After a century of silence" : Greenwood Rising -- America's new memorial museums -- Conclusion : Memory's present and future.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: African Americans -- Museums; Slavery in museum exhibits -- United States; Collective memory -- United States; Racism -- United States -- History; United States -- Race relations -- History; Noirs américains -- Musées.; Esclavage dans les objets exposés -- États-Unis.; Mémoire collective -- États-Unis.; Racisme -- États-Unis -- Histoire; États-Unis -- Relations raciales -- Histoire; HISTORY / General